THE EFFECT OF TEACHING STRATEGIES AND CURIOSITY ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Uziana Uziana; Berlin Sibarani; Anni Holila Pulungan (Universitas Negeri Medan, 2018)
The objectives of this research are to find out whether: 1) The students’ achievement in reading comprehension taught by using the Directed Reading Thinking Aactivity (DRTA) strategy was higher than taught by using the Questions-Answer Relationship (QARs) strategy. 2) The students’ achievement in reading comprehension with high curiosity was higher than that The students with low curiosity, and 3) there was interaction between teaching strategies and curiosity on The students’ achievement in reading comprehension. The population of this research was the students in grade XI of MAN Kampung (MAN KP) Teungoh Langsa in 2016/2017 school year. The total number of population of this research was 160 students. There were 6 classes. Two classes were chosen consist of 30 students of each class so 60 students were selected as sample of this research by applying multistage cluster random sampling. The research design was experimental research by using factorial design 2x2. The XI IPA2 class was taught by using Directed Reading Thinking Activity and XI IAI was taught by using Questions-Answer Relationship (QARs) Strategy. Curiosity questionnaire was conducted for classifying the students upon the high and low curiosity. Students’ achievement in reading comprehension was measured by using reading comprehension test. The data were analyzed by applying two-way analysis of variance (ANOVA) at the level of significant. The results of the data analysis proved that: 1) The students’ achievement in reading comprehension taught by Directed Reading Thinking Activity (DRTA) strategy is higher than students achievement in reading comprehension taught by Questions-Answer Relationship(QARs) Teaching strategy. 3) there was interaction between teaching strategies and curiosity on students’ achievement in reading comprehension.Keywords: Curiosity; Comprehension; Achievement; Teaching Strategies